Examining the relationships between ICT-facilitated input market and crop productivity among small-scale farmers in Southern Rwanda - Aristide Maniriho (Cogent Social Sciences, 2024)
This study investigates the interplay between ICT-facilitated input markets, crop productivity, and ICT adoption among small-scale farmers in Southern Rwanda. Supplemented by the T-test, this study employed instrumental variable approach in data analysis. Results reveal significant benefits of ICT platform use, including improved crop yields, device ownership, and resource utilization. However, geographical disparities in ICT access contribute to inequalities in agricultural outcomes. Additionally, the study demonstrates a positive effect of pesticide use and land size on crop productivity, emphasizing the need for sustainable land management practices. Factors influencing ICT adoption include crop productivity, age, and education level. While crop productivity positively impacts ICT adoption, age and education exhibit mixed relationships. Older farmers are more likely to adopt ICTs, while education levels have a counterintuitive influence. This study contributes to the literature on ICTs in agriculture, highlighting the potential benefits and challenges associated with their adoption. It emphasizes the importance of addressing the digital divide and promoting sustainable agricultural practices. Policymakers and development practitioners can leverage the findings to design effective interventions that support ICT adoption and enhance agricultural outcomes among small-scale farmers.